Development of Traditional Snack Selection Simulation App Based on MDLC as Nutritional Literacy Media for Housewives - Muhammad Arif Putra Ramadhan; Cholid Mawardi; Yudha Pradana (Jurnal Informatika dan Rekayasa Perangkat Lunak, 2026)
The increasing prevalence of Non-Communicable Diseases (NCDs) such as hypertension and diabetes in Indonesia is closely linked to excessive consumption of Sugar, Salt, and Fat (GGL). Despite government regulations, nutritional literacy among housewives who act as primary household food providers remains low, particularly in understanding complex nutritional labels on traditional snacks. This research aims to develop a nutritional literacy medium titled "Sendok Sehat," an Android-based simulation application designed to help housewives monitor and limit GGL intake. The development follows the Multimedia Development Life Cycle (MDLC) methodology, which includes the stages of concept, design, material collecting, assembly, testing, and distribution. Data was collected through direct observation of consignment stalls to build a product database and a literature study of Ministry of Health Regulation No. 30 of 2013. The application was built using Android Studio with Kotlin, utilizing Google Sheets as a cloud-based database and Figma for UI/UX design. The system features a dummy marketplace interface resembling popular ecommerce platforms to ensure ease of use. A core functional feature is the "Warning Page," which provides real-time nutritional literacy and restricts transactions if the cart exceeds the daily safety limits of 50g sugar, 2000mg salt, or 67g fat. Functional validation through Black Box Testing confirms that all features, including the GGL filter and record-keeping system, operate according to specifications. This research concludes that "Sendok Sehat" provides an interactive and practical solution to enhance nutritional literacy, empowering housewives to make healthier food choices and potentially reducing the risk of NCDs in Indonesian households.